Perlakuan Udara Panas sebagai Tindakan Karantina terhadap Biji Kedelai - Ade Syahputra; Ranta Hadi (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Introduction and dissemination of plant disease agents can be avoided through physical treatment on agricultural commodities as pre and post harvest treatment. Research was conducted to find effective quarantine treatment to eradicate fungi infestation on soybean seed. Four fungi species were chosen for this study, i.e. Cercospora sp., Sclerotium rolfsii, Colletotrichum gloeosporiodes, and Pestalotia sp. The evaluation was conducted for seed, seedling, bean oilcake, and fungi culture using hot air treatment on 45, 50, 55, 60, 65, 70 °C and control for 5 h. In general, heat treatment caused suppression significantly on seed germination and seedling growth. However, heat treatment on 45, 50 and 55 °C resulted on lower infestation of fungi on seed, and no infestation was observed on 65 and 70 °CKey words: eradication, quarantine treatment, heat treatment